Decreased β-cell function in a case with Becker muscular dystrophy accompanied by post-transplant diabetes - Kazuya Motohashi; Takaaki Murakami; Daisuke Otani; Toshihiro Nakamura; Takao Kato; Osamu Seguchi; Masahito Ogura; Daisuke Yabe; Nobuya Inagaki (Endocrinology, Diabetes & Metabolism Case Reports)
Duchenne and Becker muscular dystrophy (DMD/BMD) are genetic disorders characterized by progressive muscle degeneration due to alterations of the dystrophin protein. The degeneration of skeletal muscles and subsequent replacement with adipose tissue affect motor function as well as insulin sensing and glucose uptake in skeletal muscle, leading to the impairment of systemic glucose tolerance. Although several cases of glucose intolerance accompanied by DMD/BMD have been reported, the development of diabetes is clinically rare in adult cases with DMD/BMD. A 25-year-old man with BMD developed diabetes after receiving heart transplantation due to dilated cardiomyopathy and being on immunosuppressive drugs. Although he did not show evident glucose intolerance before heart transplantation, he demonstrated decreased β-cell function. Despite the shared background of BMD, his older brother, who had not undergone heart transplantation, showed only slightly impaired glucose tolerance and preserved β-cell function. The difference in glucose tolerance in the siblings with BMD clarifies the critical role of β-cell dysfunction in the development of diabetes in individuals with compensatory increasing demand for insulin such as DMD/BMD. In addition, the clinical importance of vigilance for post-transplant diabetes in BMD cases with immunosuppressive agents should be noted.